Home = Evim - Johnson, Tim, director; Dreamworks Animation SKG. (Hollywood : Dreamworks Animation SKG, 2015)
An alien on the run from his own people makes friends with a girl. He tries to help her on her quest, but can be an interference.
PG.
Region 2.
K-3.
Language : Turkish, English, Arabic, Polish.
Subtitle : Turkish, English, Arabic, Polish.
Keywords: Aliens -- Movie; Motion pictures -- Kids/Family Films; Movie -- animated films